2021
DOI: 10.1007/s13201-021-01457-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of heavy metals from drinking water by banana, orange and potato peel beads: a study of biosorption kinetics

Abstract: Banana, orange and potato peels (BP, OP and PP, respectively) were immobilised to produce biosorbent beads that were employed for the biosorption of heavy metals from a cocktail solution containing As(V), Cd(II), Cr(VI), Cu(II), Hg(II) and Ni(II) ions. Drinking water conditions were maintained with neutral initial pH and low concentration of the ions. Batch experiments were performed for evaluating the effect of pH in the drinking water range (6.5–8.5). Results showed a significant increase in the biosorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Numerous cheap and non-living plant-based materials [133], including potato peels [134], seed shells [135], coffee husks [136], crude olive stones [137], apple peel bead [138], citrus peels [139], shells of hazelnut and almond [140], chemically modified orange peel [141], banana peels and chemically modified banana peels [142], peels from banana, orange, and potato immobilized on sodium alginate beads [143], physic seed hull [144], rice husk [145], millet and Sorghum vulgare (Guinea corn) husks [146], rice and corn husk biochar [147], peanut husk [35], coconut husk [148], palm fruit fiber [149], neem bark [150], sugarcane bagasse [151], Rosa damascena leaf powder [152], and ajwa date pits [92], watermelon rind [130], etc., have been extensively investigated as prospective heavy metal adsorbents (Table 4). As 2+ : 18.43 [163] AD: adsorbent dose, IC: ion concentration, DHPM: dynamic high-pressure micro fluidization.…”
Section: Biomaterials As Metal Biosorbentsmentioning
confidence: 99%
“…Numerous cheap and non-living plant-based materials [133], including potato peels [134], seed shells [135], coffee husks [136], crude olive stones [137], apple peel bead [138], citrus peels [139], shells of hazelnut and almond [140], chemically modified orange peel [141], banana peels and chemically modified banana peels [142], peels from banana, orange, and potato immobilized on sodium alginate beads [143], physic seed hull [144], rice husk [145], millet and Sorghum vulgare (Guinea corn) husks [146], rice and corn husk biochar [147], peanut husk [35], coconut husk [148], palm fruit fiber [149], neem bark [150], sugarcane bagasse [151], Rosa damascena leaf powder [152], and ajwa date pits [92], watermelon rind [130], etc., have been extensively investigated as prospective heavy metal adsorbents (Table 4). As 2+ : 18.43 [163] AD: adsorbent dose, IC: ion concentration, DHPM: dynamic high-pressure micro fluidization.…”
Section: Biomaterials As Metal Biosorbentsmentioning
confidence: 99%
“…Figure 14 depicts the linear plots of the Elovich kinetic model, and the constants (a & b) were computed using the slope and deflection values of the linear plots. This model's fundamental premise is that the chemical adsorption of gases on heterogeneous adsorbent surfaces does not allow for any process (Risha et al, 2021). Table 4 shows the regression values (R 2 ) of the Elovich model, which are shown to be high, confirming the applicability of this kinetic model.…”
Section: Pseudo First Order Modelmentioning
confidence: 75%
“…The results showed that for both CV and MB dyes, the Freundlich isotherm provided the best fit, followed by the Langmuir, Temkin, and D-R isotherms. This indicates that the Freundlich isotherm model is more suitable for describing the adsorption process of CV and MB dyes by coconut shell biochar, suggesting a multilayer adsorption with heterogeneous characteristics (Nathan et al, 2021). However, the agreement of R 2 values with the Langmuir, Temkin, and D-R isotherms also indicates that these models can adequately describe the adsorption process with monolayer and heterogeneous adsorption behavior.…”
Section: Temkin Isothermmentioning
confidence: 92%